[Letters] - Melba, Nellie, Dame, 1861-1931. (1886)
Two letters. In first letter to "Dearest Una" written from ladies Athenaeum Club Melba explains that she is sorry she could not see her before she sailed and sends a thankyou for a present. In the second letter sent to Sydney, Melba thanks the reader for forwarding "Mr Child's" letter and gives the date when she will arrive in London.
Manuscript reference no.: NLA MS 1368.
Also available online
Keywords: Melba, Nellie, -- Dame, -- 1861-1931 -- Correspondence; Sopranos (Singers) -- Australia -- Correspondence